Homeownership rates, housing policies, and co-residence decisions - Nils Grevenbrock; Alexander Ludwig; Nawid Siassi (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2023)
Homeownership rates differ widely across European countries. We document that part of this variation is driven by differences in the fraction of adults co-residing with their parents. Comparing Germany and Italy, we show that in contrast to homeownership rates per household, homeownership rates per individual are very similar during the first part of the life cycle. To understand these patterns, we build an overlapping-generations model where individuals face uninsurable income risk and make consumption-saving and housing tenure decisions. We embed an explicit intergenerational link between children and parents to capture the three-way trade-off between owning, renting, and co-residing. Calibrating the model to Germany we explore the role of income profiles, housing policies, and the taste for independence and show that a combination of these factors goes a long way in explaining the differential life-cycle patterns of living arrangements between the two countries.
Keywords: D15; E21; H31; R21; 330; Homeownership; Co-residence; Overlapping generations